CLUSTER ANALYSIS INDICATORS OF THE CARDIOVASCULAR SYSTEM AS A WAY TO IDENTIFY ADAPTATION STRATEGIES TO EXAM STRESS BACHELORS OF ISU - Vladimir Vladimirovich Chrishtop; Ekaterina Sergeevna Gribkova; Natalia Kirillovna Kormilitsyna (Наука. Инновации. Технологии)
The students of Ivanovo State University in the amount of 151 people were examined indicators of respiratory and cardio-vascular systems, by measuring respiration rate, heart rate and blood pressure. Measuring carried out during practical classes in semester and after the exam. All the students were divided according to the type of adaptation into 4 groups with the cluster analysis. Were determined the average of the resulting figures of each group, the dynamics of the students. 4 adaptation strategies are revealed: the minimum, maximum and intermediate 2 - adrenal and noradrenal. Intermediate types of adaptations are transient, due to the dynamics of the students during the training. It was determined that some of the students in 1 course has a high level of adaptation, but adaptation of learning does not take place at all students of 4 course.